2002
DOI: 10.1385/abab:97:2:091
|View full text |Cite
|
Sign up to set email alerts
|

Fenton's Reagent-Mediated Degradation of Residual Kraft Black Liquor

Abstract: In this work, the effect of Fenton's reagent on the degradation of residual Kraft black liquor was investigated. The effect of Fenton's reagent on the black liquor degradation was dependent on the concentration of H2O2. At low concentrations (5 and 15 mM) of H2O2, Fenton's reagent caused the degradation of phenolic groups (6.8 and 44.8%, respectively), the reduction of reaction medium pH (18.2%), and the polymerization of black liquor lignin. At a high concentration (60 mM) of H2O2, Fenton's reagent induced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A study on the oxidation of hydrolyzed nonwood lignin showed that hydrogen peroxide (H 2 O 2 ) treatment of lignin can increase its carboxylate group and thus its water solubility . In another report, the black liquor of Caribbean Pine wood species was oxidized with hydrogen peroxide in the presence of ferrous ion . Since nonwood and wood species have different properties, the value-added products generated from these wood species would respond differently to chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the oxidation of hydrolyzed nonwood lignin showed that hydrogen peroxide (H 2 O 2 ) treatment of lignin can increase its carboxylate group and thus its water solubility . In another report, the black liquor of Caribbean Pine wood species was oxidized with hydrogen peroxide in the presence of ferrous ion . Since nonwood and wood species have different properties, the value-added products generated from these wood species would respond differently to chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…17 In another report, the black liquor of Caribbean Pine wood species was oxidized with hydrogen peroxide in the presence of ferrous ion. 18 Since nonwood and wood species have different properties, the value-added products generated from these wood species would respond differently to chemical reactions. Therefore, the results reported on the hydrogen peroxide of nonwood species may not be achieved for kraft lignin of softwood species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fenton's reagent has also been used to degrade lignin in effluents from pulp mills 22 and synthetic lignin solutions 2, achieving its complete degradation under acidic pH conditions; however, as it was expected, poor results were reported for this treatment when it was performed at basic pH values 2, 23. The combination of UV light and the use of zero‐valent iron (Fe 0 ) as heterogeneous catalyst avoids the use of iron salts and prevents the generation of iron sludge in the process.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the intensity of this band could be due to the oxidation of some of the functional groups (alcohols, phenols, or carbon-carbon double bonds) in the LW to ketones, aldehydes, or carboxylic acids. In particular, as reported in the literature (Araujo et al 2002;Wojciak et al 2007), hydrogen peroxide can cause various chemical reactions, depending on its concentration and the nature of the activators. Such reactions include the epoxidation of carbon-carbon double bonds (and the subsequent hydrolysis of the epoxy groups, forming hydroxyl groups); the oxidation of carbon-carbon double bonds into two carboxylic acid groups; the oxidation of hydroxyl or phenolic groups to ketones, aldehydes, and carboxylic acid groups; or the severe degradation of organic compounds, forming carbon dioxide and water.…”
Section: Bleaching Of Liquefied Woodmentioning
confidence: 82%